Map-dot-fingerprint (epithelial basement membrane) corneal dystrophy: A clinicopathological study - Emily Marcotte; Pedro Fraiha; Angela Fajardo; Devinder Cheema; Mahshad Darvish; Miguel Noel Burnier (The Pan-American Journal of Ophthalmology)
Background: Map-dot-fingerprint (MDF) is a corneal epithelial dystrophy affecting the basement membrane that presents bilaterally or in an asymmetric manner. Clinically, it appears as opacities or fingerprint lines and histopathologically, microcystic structures, dot-like patterns, or basement membrane thickening are commonly described features. Materials and Methods: We conducted a retrospective study on 10 cases of MDF obtained from 9 patients between 2017 to 2018 from the MUHC-McGill Ocular Pathology & Translational Research Laboratory. Results: Following histopathological evaluation with hematoxylin and eosin, periodic acid–Schiff (PAS), and in one case Alcian Blue, a final diagnosis of MDF was reached in all cases. Conclusion: This case series aims to document MDFs histopathological characteristics. To the best of our knowledge, this is the largest case series with histopathological diagnosis published, filling an important gap in the literature.